2017
DOI: 10.3390/ijms18020452
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chromatographic and Spectroscopic Methods towards the Quality Assessment of Ginger (Zingiber officinale) Rhizomes from Ecological Plantations

Abstract: The usefulness of ginger in the food industry and pharmacotherapy is strictly related to its content of various components. The study elucidates the chemical composition of Zingiber officinale rhizomes cultivated on ecological plantations on Shikoku Island (Japan). GC-MS analysis of terpene content, LC-MS determination of phenolic content, and the determination of 12 elements using AAS spectrometry were performed to give more detailed insight into the samples. Ninety-five percent of terpene composition was elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
3
42
0
2
Order By: Relevance
“…The constituents of ginger’s rhizome may be divided into two major groups: lipids and oleoresins. The latter—rich in secondary metabolites—is composed of terpenes (monoterpenes, sesquiterpenes, and sesquiterpene alcohols) in 20–25% and of phenolics–gingerols (including gingerodiones, gingerdiols, dehydrogingerdiones, and diarylheptanoids), which account for another 25% of the semi-liquid resin [ 9 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The constituents of ginger’s rhizome may be divided into two major groups: lipids and oleoresins. The latter—rich in secondary metabolites—is composed of terpenes (monoterpenes, sesquiterpenes, and sesquiterpene alcohols) in 20–25% and of phenolics–gingerols (including gingerodiones, gingerdiols, dehydrogingerdiones, and diarylheptanoids), which account for another 25% of the semi-liquid resin [ 9 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A GC-MS based qualitative analysis was performed on the three collective samples prior to further fractionation. Several compounds, which belonged to the group of terpenes were identified based on their retention indices, literature data and previous studies of the authors [ 32 ]. The identification data of major constituents are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although spice essential oils are generally safe when used in moderate amounts, some of these highly concentrated oils may irritate skin and mucous membranes, induce epilepsy, or show toxic effects in excessive dosages, especially in children who are particularly susceptible (Halicioglu, Astarcioglu, Yaprak, & Aydinlioglu, 2011; Vigan, 2010). The pharmacological benefits of spice essential oils gain more and more attention, such as their antiinfective, anticancer, antipyretic, and carminative effects (Hosseini, Nadjafi, Asareh, & Rezadoost, 2018; Koch et al., 2017). These characteristics of essential oils are strongly related to the bioactive phytochemical composition, and this composition is an important parameter for evaluating the quality of essential oils and potential application prospects.…”
Section: Spice Essential Oils and Their Major Componentsmentioning
confidence: 99%
“…Rather than the many phytochemicals in ginger that has been found to have various biological and health benefits, in 2017, a study by Koch et al, showed that ginger rhizomes contain significant amounts of certain nutrients, particularly manganese. Such finding would be imperative when discussing the impact of ginger on semen quality, in which manganese supplementation was found to enhance luteinising hormone secretion in male rats (Lee et al, ).…”
Section: Mechanistic Studiesmentioning
confidence: 99%